The future of personalized cardiovascular medicine demands 3D and 4D printing, stem cells, and artificial intelligence - Bax, Monique; Thorpe, Jordan; Romanov, Valentin (Frontiers in Sensors, 2023)
Cardiovascular diseases remain the most lethal disorders worldwide. Employing preeminent techniques is paramount for addressing this global challenge. Recent advances in lab-on-a-chip technology have the potential to transform cardiovascular medicine by providing new tools for understanding the biological variability that underlies disease and drug response. Coupling improved fabrication techniques and cardiovascular cellular models with artificial intelligence-based tools for design and analysis primes the field to model and explore cardiovascular biology more accurately than ever before. The fabrication of lab-on-a-chip systems has dramatically evolved with the development of additive manufacturing technologies. Not only can 3D printing be used to fabricate intricate microfluidic networks, but now through the incorporation of smart materials, 4D printing can change the shape and properties of devices based on external stimuli. By leveraging advances in induced pluripotent stem cells, lab-on-a-chip devices open new opportunities within personalized cardiovascular medicine. As customizable systems, devices can be fabricated and populated with donor stem cell-derived cardiovascular cells to mimic the cardiovascular system. These capabilities are only going to improve with the increasingly important role of artificial intelligence in lab-on-a-chip centric design, real-time analysis, data gathering, processing and analysis. Here, we address the potential to personalize cardiovascular medicine through the lens of advances in the fabrication of lab-on-a-chip devices, development of induced pluripotent stem cells derived engineered vasculature and heart tissues, and explore how artificial intelligence is, and will, shape this field.